2003
DOI: 10.1016/j.obstetgynecol.2003.04.001
|View full text |Cite
|
Sign up to set email alerts
|

The axial location of structural regions in the urethra: a magnetic resonance study in nulliparous women*1

Abstract: OBJECTIVE-To define and quantify the appearance and location of distinct regions of the bladder neck and urethra by using axial magnetic resonance images from healthy, continent, nulliparous women.METHODS-Seventy-eight asymptomatic, healthy, nulliparous women (mean age 29.2 ± 5.4 years) volunteered for this study. All women were proven continent on urodynamic examination. Axial proton density magnetic resonance images of the pelvic floor were analyzed at 5-mm intervals. A geometric origin was established at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 19 publications
2
20
2
Order By: Relevance
“…Axial MRI scansin each individual were reviewed to determine slices containingthe bladder base, the vesical neck and SUS, includingCU/UVS (Figure 1). 7 Figure 2 shows an exampleusing MRI. Each slice was considered to have a single predominant region, that is each slice was identified as the bladder base, vesical neck or SUS but not 2 designations.The length of the vesical neck, SUS and total urethral length were calculated by multiplying the number of slices in which these structures were seen by the 5 mm interval between each slice.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Axial MRI scansin each individual were reviewed to determine slices containingthe bladder base, the vesical neck and SUS, includingCU/UVS (Figure 1). 7 Figure 2 shows an exampleusing MRI. Each slice was considered to have a single predominant region, that is each slice was identified as the bladder base, vesical neck or SUS but not 2 designations.The length of the vesical neck, SUS and total urethral length were calculated by multiplying the number of slices in which these structures were seen by the 5 mm interval between each slice.…”
Section: Methodsmentioning
confidence: 99%
“…Strohbehn et al established the histologicaland radiological identification of its layers 3. Several studies of normal asymptomatic women showed that urethral anatomy can be visualized with MRI 47. However, to our knowledge differences in women with and without pelvic floor dysfunction have been not been directly compared and analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…Structure of the urethra and striated urogenital sphincter muscle-The length of the muscular urethra was measured as the distance from the internal urinary meatus to the distal end of the perineal membrane where the urethra becomes fibrous (23,24), and the length of the striated urogenital sphincter was assessed from this landmark to the top of the visible sphincter. Examiners were blinded to the continence status and parity of subjects.…”
Section: Functional Assessment: Urodynamic and Pelvic Floor Testingmentioning
confidence: 99%
“…In the same way, the urethral sphincter musculature can also be easily visualized and readily measured using endovaginal ultrasonography (EVUS) [15,16], intraurethral ultrasonography [17,18] and MRI [19][20][21]. The levator ani muscle and the urethral rhabdomyosphincter are both skeletal muscles.…”
Section: Introductionmentioning
confidence: 99%